Continuous and Discrete: Analog Consciousness and Digital Reduction - Barison, Marcello (Scenari, 2023)
What does it mean to think? The question, which occupies one of the many centers of the modern tradition, from Kant to Heidegger to the most recent developments in the dialogue between neuroscience and philosophy of mind, becomes all the more inevitable today. Indeed, recent developments in Artificial Intelligence make it inevitable to ask whether or not what this modern technology is capable of processing can be qualified as thought, whether or not it does or does not qualify as thought today, and, even if it does not today, whether or not it might in the future. The essay aims to address this question by making a classical approach, of essentially Aristotelian matrix, react with some of the reflections developed in this regard by Roberto Calasso, who, since La rovina di Kasch (1983), has extensively dealt with the speculative significance of the relationship between analog and digital.